2022
DOI: 10.1002/dc.24956
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of endometrial cytology and related technology

Abstract: Background Endometrial cytology is not much popular in the world, but is commonly used in a few countries. Although cytomorphological evaluation of endometrial cytology is complicating, recent advance in technology helps improve diagnostic accuracy. In addition, new reporting system, The Yokohama System, has been introduced as a standard reporting system resembling The Bethesda System of the uterine cervical cytology. Although sample standardization is one of the causes in diagnostic problem, it was solved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Endometrial cytology is not a popular procedure worldwide, whereas cervical cytology is a practical and less invasive screening tool for the detection of both cervical and endometrial cancers (24,25). The reported frequencies of cervical cytology for the detection of endometrial cancers varies from 25.5% to 45.5% (26)(27)(28)(29), while the non- II).…”
Section: Cytological Features Of Polemut-subtype (A) In the Polemut-s...mentioning
confidence: 99%
“…Endometrial cytology is not a popular procedure worldwide, whereas cervical cytology is a practical and less invasive screening tool for the detection of both cervical and endometrial cancers (24,25). The reported frequencies of cervical cytology for the detection of endometrial cancers varies from 25.5% to 45.5% (26)(27)(28)(29), while the non- II).…”
Section: Cytological Features Of Polemut-subtype (A) In the Polemut-s...mentioning
confidence: 99%
“…Endometrial glandular cells are identified in 2-3% of Pap test cytology specimens, and they may be acquired either as a result of normal shedding during the menstrual cycle or direct sampling of the lower uterine segment [10]. Diagnostic endometrial cytology sampling is also occasionally performed [11].…”
Section: Endometriummentioning
confidence: 99%
“…Endometrial carcinoma (ECa) is the most common gynecological malignant cancer, with an increased incidence and fatality rate in developed countries [ 1 ]. Some patients with ECa can be completely cured with surgery, but the outcome of patients with advanced ECa is always poor, requiring a more efficient clinical treatment strategy [ 2 ]. The diagnosis of ECa relies on histopathology, which could not identify the tumor heterogeneity of ECa or improve the efficacy of the ECa treatment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%